229k views
1 vote
For p(2) = 7 + 10x - 12x^2 - 10x^3 + 2x^4 + 3x^5, use synthetic substitution to evaluate

For p(2) = 7 + 10x - 12x^2 - 10x^3 + 2x^4 + 3x^5, use synthetic substitution to evaluate-example-1
User Xiamx
by
5.7k points

1 Answer

3 votes

Answer:

p(-3) = -428

Explanations:

Given the polynomial function expressed as:


p(x)=7+10x-12x^2-10x^3+2x^4+3x^5

Determine the value of p(-3)


\begin{gathered} p(-3)=7+10(-3)-12(-3)_^2-10(-3)^3+2(-3)^4+3(-3)^5 \\ p(-3)=7-30-12(9)-10(-27)+2(81)+3(-243) \\ p(-3)=-23-108+270+162-729 \\ p(-3)=-428 \end{gathered}

Hence the value of p(-3) is -428

User Schuess
by
5.7k points